2016
DOI: 10.1039/c5nr06319a
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped graphene frameworks with superhigh surface area: excellent electrocatalytic performance for oxygen reduction

Abstract: N-Doped carbon materials are promising candidates as alternative catalysts to noble metals in promoting the oxygen reduction reaction (ORR) in fuel cells. However, methods to further reduce the ORR overpotential and improve related kinetics remain to be developed. This study reports that N-doped graphene frameworks (NGFs) synthesized from the rapid pyrolysis of solid glycine particles in the presence of sodium carbonate, display an extremely large specific surface area (1760 m(2) g(-1)) and a graphitic-N-domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…However, the BET surface area and total pore volume of these 3 D nanoweb catalysts (241–255 m 2 g −1 , 0.96–1.04 cm 3 g −1 ) were significantly greater than those of granular NC (113 m 2 g −1 , 0.53 cm 3 g −1 ). Clearly, the unique morphology with a high BET surface area and large total pore volume is beneficial for enhanced CO 2 RR electrocatalysis because it can provide more active sites and facilitate mass transfer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the BET surface area and total pore volume of these 3 D nanoweb catalysts (241–255 m 2 g −1 , 0.96–1.04 cm 3 g −1 ) were significantly greater than those of granular NC (113 m 2 g −1 , 0.53 cm 3 g −1 ). Clearly, the unique morphology with a high BET surface area and large total pore volume is beneficial for enhanced CO 2 RR electrocatalysis because it can provide more active sites and facilitate mass transfer …”
Section: Resultsmentioning
confidence: 99%
“…Clearly,t he unique morphologyw ith ah igh BET surface area and large total pore volume is beneficial for enhanced CO 2 RR electrocatalysis because it can providem ore active sites and facilitate mass transfer. [24,28,29] The surface compositions and the corresponding chemical bondinge nvironment of all the catalysts were determined by XPS measurements. The deconvolution of the N1sp eak revealed fourd ifferent bondings tates of Na toms at 398.3, 400.2,4 01.1, and 402.9 eV,c orresponding to pyridinic N, pyrrolic N, graphitic N, and oxidized N, respectively (Figure 3a and FigureS4a in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated the ability to print concentric lamellar structures, modeled theoretically with Navier–Stokes equations, as shown in the nanoscale striations in Figure 3e. As the reaction rate can be controlled by modifying the thickness and the number of alternating layers within the structure, this approach can potentially be used to create high‐performance catalytic surfaces211,212 and cell interaction studies 213,214. This method can also be used to create composites with densely packed interfaces, improve tissue regeneration,215 and form dense hollow matrices.…”
Section: Fluid Shear Patterningmentioning
confidence: 99%
“…Therefore, controlling the amount of surface area between materials is a key design criterion for the development of artificial tissues, 12 biomimetic structures, 13,14 reinforced constructs, 11 energy harvesting systems, [15][16][17] permeable membranes, 18 sensors and supercapacitors, 10,19,20 micro-or nano-sheets 21,22 and super-catalytic surfaces. 7,8,23 State-of-theart three-dimensional (3D) printing (and bioprinting) technologies have shown their potential to create complex architectures for a wide range of applications, including electronics, microfluidics, biomedicine, and art, [24][25][26][27] and their resolution has reached the order of tens of microns. 28,29 However, these technologies fail to fabricate high resolution multi-layered microstructures efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In natural phenomena and in many relevant applications, the microstructure of a material defines its macroscale functionality. [3][4][5][6] The local rates of reaction, 7,8 heat and mass transfer, 1 ion and electron fluxes, 9,10 material strength, 2,5,11 and other important properties, depend on the extent of the interface between materials. Therefore, controlling the amount of surface area between materials is a key design criterion for the development of artificial tissues, 12 biomimetic structures, 13,14 reinforced constructs, 11 energy harvesting systems, [15][16][17] permeable membranes, 18 sensors and supercapacitors, 10,19,20 micro-or nano-sheets 21,22 and super-catalytic surfaces.…”
Section: Introductionmentioning
confidence: 99%